Telomere dynamics and hematopoietic differentiation of human DKC1-mutant induced pluripotent stem cells - Ramos, Flávia Sacilotto Donaires (2016)
Telomeres are nucleotide repetitive sequences at linear chromosome endings coated by specific proteins (shelterin) and providing chromosomal protection and stability. Telomeres shorten due to cellular mitotic division, but are maintained in cells with high proliferative capacity by telomerase, which enzymatically adds telomere repeats to the 3\' ends of the DNA strand. The telomerase complex is composed of a reverse transcriptase (TERT), an RNA component (TERC), and proteins that provide stability, as dyskerin (encoded by the DKC1 gene). Mutations in these genes may result in human diseases as dyskeratosis congenita (DC), an inherited bone marrow failure syndrome. Induced pluripotent stem cells (iPSCs) may serve to model disease, as patients\' reprogrammed cells maintain genotypic characteristics. The iPSCs overcome replicative senescence by reactivating telomerase and restoring telomere lengths. In this study, iPSCs were derived from fibroblasts of a DC patient carrying a DKC1 mutation (A353V). The effects of this mutation in telomere dynamics and hematopoietic differentiation were investigated. iPSCs were successfully derived and maintained in long-term culture without signs of spontaneous differentiation (last passage, 140). Telomeres shortened during the first passages after reprogramming, but were maintained in length after passage 20. Alternative lengthening of telomeres and genome copy number variations in the iPSCs were ruled out as responsible for this telomere behavior, suggesting that telomeres were maintained by late telomerase activation. Hematopoietic differentiation was carried out in two DKC1-mutant iPSCs clones, displaying increased capacity to generate hematopoietic lineages. In contrast to previous studies, these findings suggest that DKC1-mutant iPSCs overcome the limitations imposed by the DKC1 gene defect by eventually achieving telomere length stability and maintaining cell proliferation and selfrenewal at late passages. The model presented here may be useful for further molecular studies on telomere biology and so may serve as a platform for the screening of molecules that potentially overcome the mutant phenotype.